Gender Identity and Metadiscourse Marker Usage: An Analysis of Grade 11 Learners’ Argumentative Essays - Alcantara, Mark Kervin (Journal of Interdisciplinary Perspectives, 2025)
Effective written communication, especially in argumentative writing, is vital for academic and professional success. This study examines the unique patterns of metadiscourse usage among male, female, gay, and lesbian individuals in the Philippines, thereby broadening the existing literature on gender-related writing practices. The research emphasizes the significance of representation in academic writing, recognizing the diversity of identities and experiences. It suggests that including gay and lesbian learners in studies can enhance understanding of their language practices and promote representation. This study analyzed interactional metadiscourse markers in argumentative essays from 120 Filipino Senior High School learners who self-identified their gender identity. The cohort consisted of 30 learners identifying as male, 30 as female, 30 as gay, and 30 as lesbian. The primary data source consisted of five argumentative essays from each student, which were analyzed for interactional metadiscourse markers using manual methods and AntConc 4.20, yielding an intercoder agreement rate of 85%. Ethical considerations were paramount; all participants provided informed consent, and their anonymity was protected throughout the analysis, particularly given the sensitive nature of self-disclosed gender identity. The study highlighted significant gender differences in marker usage, with "self-mention" being the most common. Male learners exhibited a complex interplay between indirectness and assertiveness using hedges and boosters. Female learners employed hedges for caution and boosters for confidence. Lesbian and gay learners balanced caution and assertiveness, reflecting strategic communication. The study advocates for teaching metadiscourse in primary education and addressing limitations, such as a small sample size and a lack of participant demographics, in future research to improve generalizability. This approach can help students broaden their knowledge and develop diverse communication tactics, fostering self-reflection on the function of metadiscourse and its link to gender and culture in general.